SARS-CoV-2 Omicron Variant: Epidemiological Features, Biological Characteristics, and Clinical Significance - Guo, Yifei; Han, Jiajia; Zhang, Yao; He, Jingjing; Yu, Weien; Zhang, Xueyun; Wu, Jingwen; Zhang, Shenyan; Kong, Yide; Guo, Yue; Lin, Yanxue; Zhang, Jiming (Frontiers in Immunology, 2022)
The SARS-CoV-2 Omicron (B.1.1529) variant was designated as a variant of concern (VOC) by the World Health Organization (WHO) on November 26, 2021. Within two months, it had replaced the Delta variant and had become the dominant circulating variant around the world. The Omicron variant possesses an unprecedented number of mutations, especially in the spike protein, which may be influencing its biological and clinical aspects. Preliminary studies have suggested that increased transmissibility and the reduced protective effects of neutralizing antibodies have contributed to the rapid spread of this variant, posing a significant challenge to control the coronavirus disease 2019 (COVID-19) pandemic. There is, however, a silver lining for this wave of the Omicron variant. A lower risk of hospitalization and mortality has been observed in prevailing countries. Booster vaccination also has ameliorated a significant reduction in neutralization. Antiviral drugs are minimally influenced. Moreover, the functions of Fc-mediated and T-cell immunity have been retained to a great extent, both of which play a key role in preventing severe disease.